Assessing the Influence of Healthcare Service Quality on Patient Satisfaction at Dr. Soetomo General Hospital, Surabaya - Diana Sukmawati Hasan; Suwandi S Sangadji (LLDIKTI WIlayah XII Ambon, 2024)
This study aims to provide a comprehensive understanding of the relationship between healthcare service quality and patient satisfaction, and how this can be used to improve services in hospitals. Conducted at Dr. Soetomo General Hospital, Surabaya, the study involved 393 outpatients, with the sample size determined using the Slovin formula to ensure representativeness of the total outpatient population. A quantitative approach was employed, utilizing multiple regression analysis to examine the effects of five service quality dimensions: reliability, responsiveness, assurance, empathy, and tangibles on patient satisfaction. The results reveal that all dimensions positively influence patient satisfaction, although to varying degrees. Tangibles, representing the hospital's physical facilities and equipment, had the most substantial effect, underscoring the importance of a well-maintained environment. Reliability and empathy also significantly impacted satisfaction, highlighting the value patients place on consistent service delivery and compassionate care. Surprisingly, assurance—related to patients' confidence in healthcare providers' competence—showed no significant influence, suggesting that patients may already expect a high level of professional competency from the hospital staff. These findings suggest that improving hospital facilities, ensuring service reliability, and fostering empathetic care should be prioritized in service quality improvement strategies at Dr. Soetomo General Hospital. By focusing on these dimensions, hospital management can significantly enhance patient satisfaction, thereby improving healthcare outcomes and fostering greater patient loyalty.